Preparation method of refractory alloy surface ultrahigh-temperature ceramic and refractory metal silicide composite coating
The ultra-high temperature ceramic/refractory metal silicide composite coating is prepared on the surface of the refractory alloy by high-speed laser cladding and embedded silicon seepage processes, which solves the problem of insufficient anti-oxidation and ablation performance of the coating in the prior art, and achieves efficient thermal protection effect.
Patent Information
- Application Number
- CN202411807971.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art is difficult to prepare ultra-high temperature ceramic coatings with excellent anti-oxidation ablation properties and metallurgical bonding properties on the surface of refractory alloys, especially in high-temperature oxygen-rich environments, where the coating is prone to oxidation, cracking and peeling.
A high-speed laser cladding process was used to prepare a gradient structure ultra-high temperature ceramic/refractory metal ((Zr, Ta)C-Ta(W)) coating on a Ta-10W substrate, and the refractory metal phase was converted into a silicide phase through the embedding and permeable silicone process to form an ultra-high temperature ceramic/refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating.
The prepared composite coating has high density, continuous multi-layer structure, excellent resistance to high temperature ablation and metallurgical bonding properties, and can maintain a complete protection matrix for 300 seconds under plasma beam ablation of 2000-2100°C.
Smart Images

Figure CN119506871A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ultra-high temperature thermal protective coating preparation, and relates to a method for preparing a composite coating of ultra-high temperature ceramics and refractory metal silicide on the surface of a refractory alloy, a composite coating of ultra-high temperature ceramics and refractory metal silicide on the surface of a refractory alloy and a preparation method thereof, and specifically relates to a method for preparing an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating on the surface of a refractory alloy by adopting a high-speed laser cladding process and an embedded siliconizing process. Background Art
[0002] Ta-10W alloy is widely used in hot end components of aerospace due to its excellent mechanical properties at high temperatures. However, Ta-10W alloy is very easy to oxidize in high temperature oxygen-rich environment, so a thermal protection coating needs to be formed on the surface.
[0003] Ultra-high temperature ceramics have the advantages of high melting point, high temperature strength, good oxidation resistance and ablation resistance, and have great application value in the field of oxidation resistance and ablation of high temperature materials. Ultra-high temperature ceramics mainly include refractory metal borides and carbides, among which the most representative is ZrC, which has good thermal shock resistance, low density, high hardness, high melting point and moderate thermal expansion coefficient, as well as good high temperature mechanical properties and chemical stability. However, as a protective coating for metals, ceramic coatings also face problems such as mismatched thermal expansion coefficients, cracking and peeling of ceramic coatings during oxidation and ablation, and effective protection of the substrate. At present, the surface technology for preparing thermal protective coatings on the surface of refractory alloy substrates (including embedding, slurry melting, chemical vapor deposition, plasma spraying, etc.) has its own advantages and limitations. The existing coating schemes are limited by the material system, thickness, density, or bonding strength, and cannot provide ideal antioxidant protection for refractory alloy substrates.
[0004] Ceramic coatings prepared by laser surface technology can form a metallurgical bond with the metal substrate. At the same time, the rapid cooling and heating of the high-speed laser cladding process leads to finer microstructures and denser coatings. However, current research has confirmed that due to the extremely high energy density of the laser and the inherent brittleness of ultra-high temperature ceramic (UHTC) materials, it is difficult to produce complete UHTC coatings using laser surface technology. In recent years, with the emergence and development of high-speed laser cladding technology, it is expected to solve the above problems. The high-speed laser cladding process can directly apply most of the laser energy to the flying powder, while reducing the energy acting on the substrate, which can effectively regulate the energy between the powder and the substrate (while the traditional laser heat source coating preparation technology directly applies almost all of the energy to the substrate (sub) surface / inside the molten pool, which will cause brittle cracking and peeling of the prepared ultra-high temperature ceramic coating). However, the coating prepared by high-speed laser cladding still inevitably contains a small amount of refractory metal phase, which is not conducive to the high-temperature ablation resistance of the coating. Therefore, how to combine the advantages of the above-mentioned processes to prepare a composite coating with excellent anti-oxidation and ablation properties and metallurgical bonding properties is a key challenge faced in the preparation of ultra-high temperature ceramic-based composite coatings.
[0005] At present, the preparation process and advantages and disadvantages of anti-oxidation ablative coatings are as follows: (1) Physical vapor deposition: The commonly used method is magnetron sputtering, which can be used to prepare coatings of high melting point materials such as SiC, HfB2 and ZrB2. However, the thickness of the prepared coating is thin, usually not exceeding 50μm, and it takes longer time than other preparation methods; (2) Chemical vapor deposition: It can prepare high melting point coatings under low temperature and can precisely control the composition of the coatings. However, the deposition efficiency of the coatings is low and the production cost is high. The raw gas and waste gas after the reaction are toxic, flammable, and explosive, which can easily cause safety hazards. (3) Slurry sintering method: It has the advantages of simple process, low equipment requirements, no influence from substrate shape, low preparation cost and easy industrialization. However, the coating thickness uniformity prepared by this process is poor, there are many defects, and the temperature resistance of the prepared silicide system does not exceed 1700℃. (4) Embedding method: It has the advantages of simple equipment, simple operation, good combination of coating and substrate, ability to achieve co-penetration of multiple elements at the same time, ability to prepare coatings with excellent performance for products with complex shapes, and low environmental pollution. However, the coating thickness is difficult to control and may have a certain impact on the substrate. The coating thickness is usually less than 200µm, otherwise the silicide layer is prone to brittle cracking. In addition, the material system is limited to silicide or aluminide, and the oxidation resistance temperature does not exceed 1700℃. (5) Plasma spraying: It has the advantages of fast coating deposition rate, easy control of coating thickness, simple operation, and suitability for large-scale production. However, plasma spray coatings have disadvantages such as high porosity and poor bonding with the substrate. Oxygen can easily invade and oxidize the substrate during service.
[0006] Therefore, in order to meet the demand for thermal protection on the surface of refractory metal hot-end components serving in extremely high temperature (≥1800℃) environments, it is crucial to carry out research on new ultra-high temperature thermal protection coatings. Summary of the invention
[0007] In view of the problems existing in the ultra-high temperature ceramic coatings in the prior art, and taking into account the advantages and disadvantages of the existing coating preparation processes and materials, as well as the failure forms of anti-ablation coatings, the present invention provides a method for preparing a composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy, a composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy and a preparation method thereof, and also an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-Ta(W)) coating on the surface of a refractory alloy and a preparation method thereof, specifically: firstly, a gradient structured ultra-high temperature ceramic / refractory metal (Zr, Ta)C-Ta(W) coating is prepared on a Ta-10W substrate by a high-speed laser cladding process; further, an embedded siliconization process is used to convert the refractory metal phase in the (Zr, Ta)C-Ta(W) coating into a corresponding silicide phase, thereby obtaining a highly dense, thick, continuous multilayer structured ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating.
[0008] The technical solution of the present invention is as follows: A method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2), the preparation method is as follows: (1) ZrC ceramic powder with good sphericity was prepared by spray granulation method; (2) A gradient structured ultrahigh temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating was prepared on a Ta-10W substrate using a high-speed laser cladding process; (3) The refractory metal phase in the (Zr, Ta)C-Ta(W) coating is converted into the corresponding silicide phase by the embedded siliconization process, thereby obtaining an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating.
[0009] The novel composite coating prepared in the present invention has the properties of uniform tissue composition, high hardness, high density, continuous multilayer structure, high temperature ablation resistance and the like.
[0010] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) on the surface of a refractory alloy, and also a method for preparing an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating on the surface of a refractory alloy by using a high-speed laser cladding process and an embedded siliconizing process, comprising the following steps: S1. Spray granulation ZrC powder: S1-1. Prepare slurry: stir high-purity zirconium carbide ceramic powder, purified water, polyvinyl alcohol (PVA), polyethylene glycol (PEG), and n-butanol in a ratio of 100 g: 82 mL: 16 g: 2 g: 1 mL with a mechanical stirrer at a speed of 500 rpm for 2 h to obtain a ceramic slurry for spray granulation; S1-2, spray granulation: the ceramic slurry is granulated by a spray granulation device to obtain a nearly spherical ZrC powder, wherein the process parameters of the spray granulation device are: air inlet temperature 240°C, air outlet temperature 160°C, atomizer frequency 50Hz, peristaltic pump speed 10rpm; After granulation, the ZrC powder is collected and dried, and sieved with a 180-mesh standard sieve to obtain -180-mesh ZrC powder, which is used for high-speed laser cladding to prepare coatings; S2. Preparation of ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating by high-speed laser cladding: S2-1. Pre-treatment of the Ta-10W substrate surface by rust removal and oil removal: polish the substrate with #200, #400, #600 and #800 sandpaper for 2 minutes each, and then use acetone or anhydrous ethanol to ultrasonically clean the surface to remove oil and impurities, with an ultrasonic power of 150W for a total of 15 minutes; S2-2, the ZrC ceramic powder obtained in S1-2 is loaded into the powder feeder of the high-speed laser cladding equipment, and then fed into the high-speed laser cladding equipment equipped with a synchronous powder feeding head, and the laser focus formed by the high-speed cladding laser head emitting laser is overlapped with the powder spot focus formed by the synchronous powder feeding head feeding powder, and then the overlap position of the two focal points is adjusted to be 1 mm above the surface of the substrate, and the substrate is subjected to high-speed laser cladding in a local inert gas protection atmosphere, and zirconium carbide undergoes phase change under the action of the high-energy laser beam to form an ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating having both ceramic phase and metal phase; The process parameters of high-speed laser cladding were as follows: laser power was set to 2500 W, scanning rate was 80 mm / s, and overlap rate was 85%; S3. Ball milling to prepare powder for embedded siliconization process: S3-1, powder for embedded siliconization process, weigh 25% Si powder, 68% Al2O3 powder, 5% Y2O3 powder and 2% NaF powder according to the mass ratio; Si powder is used as silicon source, Al2O3 powder and Y2O3 powder are used as dispersants, and NaF powder is used as activator; Among them, the particle size of Si powder is 300 mesh, purity is 99.99%; the particle size of Al2O3 powder is 100 mesh, purity is 99.99%; the particle size of Y2O3 powder is 100 mesh, purity is 99.99%; the particle size of NaF powder is 100 mesh, purity is 99.99%; S3-2, placing the weighed powder raw material in a ball mill, using a planetary mill to grind the powder to fineness and mix it evenly, with a ball-to-material ratio of 2:1, a ball mill speed of 250r / min, and a ball milling time of 5h to obtain powder for embedded siliconization process; S4. Preparation of ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating by embedded siliconization process: S4-1: Cut the ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating prepared in S2 into a 28mm×18mm×5mm rectangular block, and use sandpaper to remove the wire cutting marks on all surfaces of the sample except the surface where the coating is located, until the surface is flat, smooth and scratch-free; select a crucible with a capacity of 30ml, and in order to ensure a certain distance from the crucible mouth, the mixed infiltration dosage used for a single siliconization is 24g; S4-2: Take out the siliconized powder after ball milling in S3-2, weigh 12g and put it into the crucible for compaction, put the sample to be siliconized into the center area, and then weigh 10g of powder for embedding siliconization process to cover the sample and compact it, mix neutral alumina and silica sol in appropriate amounts to prepare a sealing slurry to seal the crucible cover and the crucible; put the sealed crucible on the corundum boat and push it to the center of the heating tube of the tubular furnace, so that the crucible is fixed in the highest temperature area during heating and insulation and is heated evenly; S4-3: Place the crucible on the corundum boat and place it in the center of the tubular furnace. Evacuate the crucible. After the pressure in the tube drops to 0.1MPa, continue to evacuate for 10 minutes, and then turn off the mechanical pump. Pass argon gas until the pressure in the tube rises to atmospheric pressure. 10 minutes later, start heating and continue ventilating. The argon flow rate is 100ml / min. Set the heating and cooling programs of the tubular furnace with a heating rate of 10℃ / min, a holding temperature of 1200℃, a holding time of 24h, a cooling rate of 10℃ / min, and cooling to room temperature to obtain a composite coating of ultra-high temperature ceramics and refractory metal silicides ((Zr, Ta)C-TaSi2) on the surface of a refractory alloy. The obtained composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy has a continuous multilayer structure, with a top layer of (Zr, Ta)C-TaSi2 and a transition layer of (Zr, Ta)C-Ta(W), the coating and the substrate have a metallurgical bonding interface; density>98.5%, thickness≥300μm, average hardness>1568.34 Hv 0.5 (The highest hardness is 1673.67 Hv 0.5 ), can last for 300 seconds under plasma beam ablation conditions of 2000-2100℃ and completely protect the substrate from being damaged.
[0011] The present invention also relates to a composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy, which is obtained by using the above-mentioned method for preparing a composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy. The obtained composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy has a continuous multi-layer structure, a top layer of (Zr, Ta)C-TaSi2, a transition layer of (Zr, Ta)C-Ta(W), and a metallurgical bonding interface between the coating and the substrate; the density is >98.5%, the thickness is ≥300μm, and the average hardness is >1568.34 Hv 0.5 (The highest hardness is 1673.67 Hv 0.5 ), can maintain 300 seconds under the condition of plasma beam ablation at 2000-2100℃ to completely protect the substrate from being damaged; significantly better than the existing technology, and the process has the advantages of short preparation cycle, controllable coating thickness, and complex shapes that can be prepared, specifically: ① The density of the composite coating is >98.5%, which effectively blocks oxygen and has controllable thickness. A thick coating with a thickness of more than 300μm can be prepared according to demand, realizing a continuous transition from ultra-high temperature ceramic / refractory metal silicide composite coating, ultra-high temperature ceramic / refractory metal transition layer to refractory alloy substrate; ② The composite coating was subjected to ablation test under plasma beam. After 300s of ablation at 1900℃, an oxide layer was produced on the surface of the ablation center area. With the change of temperature, the composition of the oxide layer also changed to a certain extent, mainly consisting of ZrO2 and SiO2. That is, after ablation, the coating surface was transformed from a mixture of Al2O3, TaSi2, and ZrSi2 ceramic phases to an oxide layer composed of Al2O3, ZrO2, and SiO2 to resist the subsequent high-temperature airflow erosion, so that the sub-surface siliconized layer below was not affected by ablation and was in a completely protected state. ③ After 300s of plasma beam ablation at 2000-2100℃, the coating surface is slightly damaged, and the generated oxides such as SiO2 are washed away, causing the subsequent sub-surface layer to be oxidized, but the coating can still completely protect the substrate from oxidation.
[0012] Compared with the prior art, the present invention has the following advantages: 1. The present invention discloses a method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy. A method for preparing a composite coating of ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) on the surface of a refractory alloy is proposed. A ZrC ceramic powder with a particle size of micrometer level and good sphericity is prepared by a spray granulation method. The composite coating with excellent anti-oxidation and ablation properties and metallurgical bonding properties is prepared by combining the advantages of a high-speed laser cladding process and an embedded siliconization process. First, a gradient-structured ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating is prepared on a Ta-10W substrate by a high-speed laser cladding process. Further, an embedded siliconization process is used to convert the refractory metal phase in the composite coating into a corresponding silicide phase, thereby obtaining an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating with a high density, large thickness and continuous multilayer structure.
[0013] 2. A method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy according to the present invention: ① The micron-sized ZrC ceramic powder with good sphericity obtained by spray granulation method has a particle size of 80 µm, good fluidity, and is not easy to get stuck, which is conducive to subsequent high-speed laser cladding; ② The ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) composite coating with a gradient structure prepared on a Ta-10W substrate by a high-speed laser cladding process has the advantage of metallurgical bonding, and there is no need to worry about the potential risk of thermal protection coating falling off during service; ③ The (Zr, Ta)C-Ta(W) coating is silicified by the embedded siliconization process, aiming to convert the refractory metal phase in the (Zr, Ta)C-Ta(W) coating into the corresponding silicide phase, thereby obtaining an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating; the longer the embedded siliconization insulation time, the thicker the siliconization layer. During the embedded siliconization process, the formation of silicide causes the coating to expand to a certain extent as a whole, which has a positive effect on increasing the density and reducing the porosity inside the coating. At the same time, the expansion will cause compressive stress in the coating, and long-term high-temperature treatment is beneficial to improving the bonding strength between the coating and the substrate.
[0014] 3. The method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy described in the present invention realizes the preparation of a new type of ultra-high temperature multiphase ceramic coating (i.e., a composite of ultra-high temperature ceramic and high temperature silicide ceramic phase) as a whole. The thermal protective coating has a density of >98.5%, can effectively block oxygen, and has controllable thickness. A thick coating with a thickness of more than 300 μm can be prepared according to demand; and a continuous transition from the ultra-high temperature ceramic / refractory metal silicide composite coating, the ultra-high temperature ceramic / refractory metal transition layer to the refractory alloy substrate is realized.
[0015] 4. The present invention discloses a composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy. The coating sample is subjected to ablation test under a plasma beam. After 300 seconds of beam ablation at 1800-1900°C, an oxide layer is generated on the surface of the ablation center area. As the temperature changes, the composition of the oxide layer also changes to a certain extent, mainly consisting of two components, ZrO2 and SiO2. That is, after ablation, the coating surface is transformed from a mixture of various ceramic phases such as Al2O3, TaSi2, and ZrSi2 into an oxide layer with components of Al2O3, ZrO2, and SiO2, which jointly resist the erosion of subsequent high-temperature airflow, so that the sub-surface siliconized layer below is not affected by the ablation and is in a completely protected state. After 300 seconds of beam ablation at 2000-2100°C, the coating surface is slightly damaged, and the oxides such as SiO2 generated at the same time are washed away, so that the subsequent sub-surface layer is oxidized, but the coating can still completely protect the substrate from oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with Embodiment 1 of the present invention, they are used to explain the present invention and do not constitute a limitation to the present invention.
[0017] Figure 1 This is a SEM image of ZrC powder prepared by spray granulation in the method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy according to the present invention; Figure 2A cross-sectional SEM image of an ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating according to a method for preparing an ultra-high temperature ceramic and refractory metal silicide composite coating on a refractory alloy surface according to the present invention; Figure 3 This is a cross-sectional SEM image of a composite coating of ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 on the surface of a refractory alloy prepared in Example 1 of the present invention; Figure 4 XRD pattern of a composite coating of ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 on the surface of a refractory alloy prepared in Example 1 of the present invention; Figure 5 The ablation curve of a composite coating of ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 on the surface of a refractory alloy prepared in Example 1 of the present invention, which was ablated at 1800-1900°C for 300s, and the surface morphology of the coating during ablation; Figure 6 The cross-sectional morphology of a composite coating of ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 on the surface of a refractory alloy prepared in Example 1 of the present invention after ablation at 1800-1900°C for 300s: Figure 7 The ablation curve of a composite coating of ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 on the surface of a refractory alloy prepared in Example 2 of the present invention after ablation at 2000-2100°C for 300s and the surface morphology of the coating during ablation; Figure 8 This is a cross-sectional morphology of a composite coating of ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 on the surface of a refractory alloy prepared in Example 2 of the present invention after ablation at 2000-2100°C for 300s; Fig. 9 This is a macroscopic morphology of the surface of the ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating prepared in the comparative example of the present invention after ablation at 2000-2100°C for 12s. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0019] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0021] The present invention will be described in more detail below with reference to the accompanying drawings. In each of the accompanying drawings, the same elements are represented by similar reference numerals. For the sake of clarity, the various parts in the accompanying drawings are not drawn to scale.
[0022] Features described and / or illustrated with respect to one embodiment may be used in the same or similar manner in one or more other embodiments, combined with features in other embodiments, or substituted for features in other embodiments.
[0023] Embodiment 1: A method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy comprises the following steps: Step 1: Prepare slurry: stir high-purity zirconium carbide ceramic powder, purified water, PVA (polyvinyl alcohol), PEG (polyethylene glycol), and n-butanol in a ratio of 100 g: 82 mL: 16 g: 2 g: 1 mL with a mechanical stirrer (speed 500 rpm) for 2 hours to obtain a ceramic slurry for spray granulation; Step 2: Spray granulation: The ceramic slurry is granulated using a spray granulation device to obtain a nearly spherical ZrC powder; the process parameters of the spray granulation device are: air inlet temperature 240°C, air outlet temperature 160°C, atomizer frequency 50Hz, peristaltic pump speed 10rpm; after granulation, the collected powder is dried and sieved using a 180-mesh standard sieve to obtain -180-mesh powder for high-speed laser cladding to prepare the coating; Step 3: Pre-treatment of the Ta-10W substrate surface by rust removal and oil removal: Grind the substrate with #200, #400, #600 and #800 sandpaper for 2 minutes each, and then use acetone or anhydrous ethanol to ultrasonically clean the surface to remove oil and impurities, with an ultrasonic power of 150W for a total of 15 minutes; Step 4: Load the ZrC ceramic powder into the powder feeder of the high-speed laser cladding equipment, and feed it into the high-speed laser cladding equipment equipped with a synchronous powder feeding head. Overlap the laser focus formed by the high-speed cladding laser head emitting laser and the powder spot focus formed by the synchronous powder feeding head feeding powder. Then adjust the overlapping position of the two focal points to be 1mm above the substrate surface, and perform high-speed laser cladding on the substrate under a local inert gas protection atmosphere. Zirconium carbide undergoes phase change under the action of the high-energy laser beam to form a composite coating with both ceramic phase and metal phase. The process parameters of high-speed laser cladding are: laser power is set to 2500W, scanning rate is 80mm / s, and overlap rate is 85%; Step 5: The powder for embedding siliconization process uses Si powder as silicon source, Al2O3 and Y2O3 powder as dispersants, and NaF powder as activator; 25% Si powder, 68% Al2O3, 5% Y2O3 and 2% NaF are weighed according to the mass ratio; among them, Si particle size is 300 mesh, purity is 99.99%, Al2O3 particle size is 100 mesh, purity is 99.99%, Y2O3 particle size is 100 mesh, purity is 99.99%, NaF particle size is 100 mesh, purity is 99.99%; Step 6: Place the weighed powder raw materials in a ball mill, and use a planetary mill to grind the powders to fineness and mix them evenly; the ball-to-material ratio is 2:1, the ball mill speed is 250r / min, and the ball milling time is 5h; Step 7: Cut the high-speed laser cladding ZrC ultra-high temperature ceramic coating into a 28mm×18mm×5mm rectangular block, and use sandpaper to remove the wire cutting marks on all surfaces of the sample except the surface where the coating is located, until the surface is flat, smooth and scratch-free; select a crucible with a capacity of 30ml, and in order to ensure a certain distance from the crucible mouth, the mixed infiltration dosage used for a single siliconization is 24g; Step 8: Take out the siliconized powder after ball milling, weigh 12g and put it into the crucible for compaction, put the sample to be siliconized into the center area, and then weigh 10g of the infiltrant powder again to cover the sample and compact it; mix the neutral alumina and silica sol in appropriate amounts to prepare a sealing slurry to seal the crucible cover and the crucible; put the sealed crucible on the corundum boat and push it to the center of the tubular furnace heating tube, so that the crucible is fixed in the highest temperature area and heated evenly during heating and insulation; Step 9: Place the crucible on the corundum boat, place it in the center of the tube furnace, evacuate, and continue to evacuate for 10 minutes after the pressure in the tube drops to 0.1MPa, then turn off the mechanical pump; introduce argon gas until the pressure in the tube rises to atmospheric pressure for 5 minutes, start heating, and continue ventilation; the argon gas flow rate is 100ml / min; set the heating and cooling programs of the tube furnace, the heating rate is 10℃ / min, the holding temperature is 1200℃, the holding time is 24h, and the cooling rate is 10℃ / min to cool to room temperature; Step 10: Use plasma beam to perform plasma beam ablation test on the ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating sample, the ablation temperature is 1800-1900℃, and the ablation time is 300s; By observing and analyzing the surface of the sample after ablation, it was found that there were slight ablation marks on the coating surface, with a small amount of ablation holes, but no obvious cracks on the surface; result: In view of the fact that in Example 1, after the prepared coating was ablated under a beam at 1800-1900°C for 300s, only the surface of the coating suffered obvious ablation damage, while the inner layer of the coating remained intact, and had good anti-oxidation and ablation performance, in Example 2, the coating was tested by ablation under a beam at 2000-2100°C for 300s, and the test results are shown in Example 2.
[0024] Figure 1 This is a SEM image of ZrC powder prepared by spray granulation in the method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy described in step 2 of Example 1; Figure 2 This is a cross-sectional SEM image of an ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating in the method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on a refractory alloy surface described in step 4 of Example 1; Figure 3 This is a cross-sectional SEM image of the composite coating of ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) after the embedded siliconization process in step nine of Example 1; Figure 4 The XRD pattern of the surface of the composite coating of ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) after the embedding siliconization process in step nine of Example 1; Figure 5 The ablation curve of the ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 composite coating ablated at 1800-1900°C for 300s in step 10 of Example 1 and the surface morphology of the coating during ablation; Figure 6 This is a cross-sectional morphology of the ultrahigh temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 composite coating after ablation at 1800-1900°C for 300s in step 10 of Example 1.
[0025] Example 2 A method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy comprises the following steps: Step 1: Prepare slurry: stir high-purity zirconium carbide ceramic powder, purified water, PVA (polyvinyl alcohol), PEG (polyethylene glycol), and n-butanol in a ratio of 100 g: 82 mL: 16 g: 2 g: 1 mL with a mechanical stirrer (speed 500 rpm) for 2 hours to obtain a ceramic slurry for spray granulation; Step 2: Spray granulation: The ceramic slurry is granulated using a spray granulation device to obtain a nearly spherical ZrC powder; the process parameters of the spray granulation device are: air inlet temperature 240°C, air outlet temperature 160°C, atomizer frequency 50Hz, peristaltic pump speed 10rpm; after granulation, the collected powder is dried and sieved using a 180-mesh standard sieve to obtain -180-mesh powder for high-speed laser cladding to prepare the coating; Step 3: Pre-treat the surface of the Ta-10W substrate by removing rust and oil; polish the substrate with #200, #400, #600 and #800 sandpaper for 2 minutes each, and then use acetone or anhydrous ethanol to ultrasonically clean the surface to remove oil and impurities, with an ultrasonic power of 150W for a total of 15 minutes; Step 4: Load the ZrC ceramic powder into the powder feeder of the high-speed laser cladding equipment, and feed it into the high-speed laser cladding equipment equipped with a synchronous powder feeding head. Overlap the laser focus formed by the high-speed cladding laser head emitting laser and the powder spot focus formed by the synchronous powder feeding head feeding powder. Then adjust the overlapping position of the two focal points to be 1mm above the substrate surface, and perform high-speed laser cladding on the substrate under a local inert gas protection atmosphere. Zirconium carbide undergoes phase change under the action of the high-energy laser beam to form a composite coating with both ceramic phase and metal phase. The process parameters of high-speed laser cladding are: laser power is set to 2500W, scanning rate is 80mm / s, and overlap rate is 85%; Step 5: The powder for embedding siliconization process uses Si powder as silicon source, Al2O3 and Y2O3 powder as dispersants, and NaF powder as activator; 25% Si powder, 68% Al2O3, 5% Y2O3 and 2% NaF are weighed according to the mass ratio; among them, Si particle size is 300 mesh, purity is 99.99%, Al2O3 particle size is 100 mesh, purity is 99.99%, Y2O3 particle size is 100 mesh, purity is 99.99%, NaF particle size is 100 mesh, purity is 99.99%; Step 6: Place the weighed powder raw materials in a ball mill, and use a planetary mill to grind the powders to fineness and mix them evenly; the ball-to-material ratio is 2:1, the ball mill speed is 250r / min, and the ball milling time is 5h; Step 7: Cut the high-speed laser cladding ZrC ultra-high temperature ceramic coating into a 28mm×18mm×5mm rectangular block, and use sandpaper to remove the wire cutting marks on all surfaces of the sample except the surface where the coating is located, until the surface is flat, smooth and scratch-free; select a crucible with a capacity of 30ml, and in order to ensure a certain distance from the crucible mouth, the mixed infiltration dosage used for a single siliconization is 24g; Step 8: Take out the siliconized powder after ball milling, weigh 12g and put it into the crucible for compaction, put the sample to be siliconized into the center area, and then weigh 10g of the infiltrant powder again to cover the sample and compact it; mix the neutral alumina and silica sol in appropriate amounts to prepare a sealing slurry to seal the crucible cover and the crucible; put the sealed crucible on the corundum boat and push it to the center of the tubular furnace heating tube, so that the crucible is fixed in the highest temperature area and heated evenly during heating and insulation; Step 9: Place the crucible on the corundum boat, place it in the center of the tube furnace, evacuate, and continue to evacuate for 10 minutes after the pressure in the tube drops to 0.1MPa, then turn off the mechanical pump; introduce argon gas until the pressure in the tube rises to atmospheric pressure for 5 minutes, start heating, and continue ventilation; the argon gas flow rate is 100ml / min; set the heating and cooling programs of the tube furnace, the heating rate is 10℃ / min, the holding temperature is 1200℃, the holding time is 24h, and the cooling rate is 10℃ / min to cool to room temperature; Step 10: Use plasma beam to conduct ultra-high temperature ablation test on ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating samples, with an ablation temperature of 2000-2100℃ and an ablation time of 300s.
[0026] result: After 300s of beam ablation at 2000-2100℃, the coating surface was slightly damaged, and the generated oxides such as SiO2 were washed away, causing the subsequent sub-surface layer to be oxidized, but the coating could still completely protect the substrate from oxidation.
[0027] Figure 7 The ablation curve of the ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 composite coating ablated at 2000-2100°C for 300s in step 10 of Example 2 and the surface morphology of the coating during ablation; Figure 8 This is a cross-sectional morphology of the ultra-high temperature ceramic and refractory metal silicide (Zr, Ta) C-TaSi2 composite coating after ablation at 2000-2100°C for 300s in Step 10 of Example 2. Comparative Example: The difference between the comparative example and Example 1 is that the comparative example 1 does not perform the embedded siliconization process step, and directly performs an ablation test on the ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) coating, while Example 1 performs the embedded siliconization process step, and performs an ablation test on the embedded siliconized high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating; The preparation method of the comparative example comprises the following steps: Step 1: Prepare slurry: stir high-purity zirconium carbide ceramic powder, purified water, PVA (polyvinyl alcohol), PEG (polyethylene glycol), and n-butanol in a ratio of 100 g: 82 mL: 16 g: 2 g: 1 mL with a mechanical stirrer (speed 500 rpm) for 2 hours to obtain a ceramic slurry for spray granulation; Step 2: Spray granulation: The ceramic slurry is granulated using a spray granulation device to obtain a nearly spherical ZrC powder; the process parameters of the spray granulation device are: air inlet temperature 240°C, air outlet temperature 160°C, atomizer frequency 50Hz, peristaltic pump speed 10rpm; after granulation, the collected powder is dried and sieved using a 180-mesh standard sieve to obtain -180-mesh powder for high-speed laser cladding to prepare the coating; Step 3: Pre-treat the surface of the Ta-10W substrate by removing rust and oil; polish the substrate with #200, #400, #600 and #800 sandpaper for 2 minutes each, and then use acetone or anhydrous ethanol to ultrasonically clean the surface to remove oil and impurities, with an ultrasonic power of 150W for a total of 15 minutes; Step 4: Load the ZrC ceramic powder into the powder feeder of the high-speed laser cladding equipment, and feed it into the high-speed laser cladding equipment equipped with a synchronous powder feeding head. Overlap the laser focus formed by the high-speed cladding laser head emitting laser and the powder spot focus formed by the synchronous powder feeding head feeding powder. Then adjust the overlapping position of the two focal points to be 1mm above the substrate surface, and perform high-speed laser cladding on the substrate under a local inert gas protection atmosphere. Zirconium carbide undergoes phase change under the action of the high-energy laser beam to form a composite coating with both ceramic phase and metal phase. The process parameters of high-speed laser cladding are: laser power is set to 2500W, scanning rate is 80mm / s, and overlap rate is 85%; Step 5: Use plasma beam to perform ultra-high temperature ablation test on the sample, the ablation temperature is 2000-2100℃, and the ablation time is 12s; result: By comparing the comparative example with Examples 1-2, the coatings obtained in Examples 1 and 2 can achieve ideal anti-ablation performance only after being treated with the embedded siliconization process, while the coating obtained in Comparative Example 1 was not treated with the embedded siliconization process, so the coating was ablated and damaged after ablation at 2000-2100°C for 12s.
[0028] Fig. 9 The surface morphology of the sample after ablation at a temperature of 2000-2100°C and ablation time of 12s in step 5 of the comparative example is shown in FIG. Fig. 9 As shown: After the (Zr, Ta)C-Ta(W) coating that has not been treated with the embedded siliconization process was continuously ablated at 2000-2100℃ for 12s, the coating underwent destructive ablation and the substrate was exposed and melted.
[0029] Results and Discussion: It can be seen from the above embodiments that the present invention provides a method for preparing an ultra-high temperature ceramic and refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating on the surface of a refractory alloy. Combining the advantages of the high-speed laser cladding process and the embedded siliconization process, the ultra-high temperature ceramic / refractory metal ((Zr, Ta)C-Ta(W)) composite coating with a gradient structure prepared on a Ta-10W substrate by the high-speed laser cladding process has the advantage of metallurgical bonding, and there is no need to worry about the potential risk of thermal protection coating falling off during service. Subsequently, the (Zr, Ta)C-Ta(W) coating is silicided by an embedded siliconization process, aiming to convert the refractory metal phase in the composite coating into the corresponding silicide phase, thereby obtaining an ultra-high temperature ceramic / refractory metal silicide ((Zr, Ta)C-TaSi2) composite coating, and preparing a composite coating with both excellent anti-oxidation and ablation properties and metallurgical bonding properties.
[0030] It can be seen from the comparative example that when the coating is not combined using the process used in the present invention, the presence of the metal phase in the coating will cause the coating to fail quickly during the ablation process.
[0031] In summary, the present invention realizes the preparation of a new type of ultra-high temperature composite ceramic coating (i.e., a composite of ultra-high temperature ceramic and high temperature silicide ceramic phase) as a whole. The density of the composite coating is >98.5%, which can effectively block oxygen, and the thickness is controllable. A thick coating with a thickness of more than 300 μm can be prepared according to demand. A continuous transition from ultra-high temperature ceramic / refractory metal silicide composite coating, ultra-high temperature ceramic / refractory metal transition layer to refractory alloy substrate is realized. The coating sample is subjected to ablation test under a plasma beam. Under a beam ablation of 1800-1900°C, an oxide layer is produced on the surface of the ablation center area. With the change of temperature, the composition of the oxide layer also changes to a certain extent, mainly the two components of ZrO2 and SiO2, that is, after ablation, the coating surface is transformed from a mixture of Al2O3, TaSi2, and ZrSi2 ceramic phases into an oxide layer composed of Al2O3, ZrO2 and SiO2 to jointly resist the subsequent high-temperature airflow scouring, so that the sub-surface siliconized layer below is not affected by ablation and is in a completely protected state. Under beam ablation at 2000-2100℃, the coating surface is slightly damaged, and the generated oxides such as SiO2 are washed away, causing the subsequent sub-surface layer to be oxidized, but the coating can still completely protect the substrate from oxidation.
[0032] It is important to add that although the present invention uses zirconium carbide (ZrC) ultra-high temperature ceramics as powder feed, the scope of protection is not limited to ZrC ultra-high temperature ceramics. Other ultra-high temperature ceramics (such as ZrB2, etc.) systems can also be tried and should be included in the scope of protection of this patent.
[0033] Similarly, although the present invention uses Ta-10W refractory metal as the matrix material, the scope of protection is not limited to Ta-10W refractory metal. Other refractory metal systems (such as Ta-12W, molybdenum alloy, etc.) can also be tried and should also be included in the scope of protection of this patent.
[0034] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy, characterized in that: The following steps are involved: S1. Spray granulation ZrC powder: S1-1. Prepare slurry: stir high-purity zirconium carbide ceramic powder, purified water, polyvinyl alcohol, polyethylene glycol, and n-butanol in a ratio of 100 g: 82 mL: 16 g: 2 g: 1 mL with a mechanical stirrer at a speed of 500 rpm for 2 h to obtain a ceramic slurry for spray granulation; S1-2, spray granulation: the ceramic slurry is granulated by a spray granulation device to obtain a nearly spherical ZrC powder, wherein the process parameters of the spray granulation device are: air inlet temperature 240°C, air outlet temperature 160°C, atomizer frequency 50Hz, peristaltic pump speed 10rpm; After granulation, the ZrC powder is collected and dried, and sieved with a 180-mesh standard sieve to obtain -180-mesh ZrC powder, which is used for high-speed laser cladding to prepare coatings; S2. High-speed laser cladding to prepare ultra-high temperature ceramic / refractory metal coatings: S2-1. Pre-treatment of the Ta-10W substrate surface by rust removal and oil removal: polish the substrate with #200, #400, #600 and #800 sandpaper for 2 minutes each, and then use acetone or anhydrous ethanol to ultrasonically clean the surface to remove oil and impurities, with an ultrasonic power of 150W for a total of 15 minutes; S2-2, loading the ZrC ceramic powder obtained in S1-2 into the powder feeder of the high-speed laser cladding equipment, and feeding it into the high-speed laser cladding equipment equipped with a synchronous powder feeding head, overlapping the laser focus formed by the high-speed cladding laser head emitting laser and the powder spot focus formed by the synchronous powder feeding head feeding powder, and then adjusting the overlapping position of the two focal points to be located 1 mm above the surface of the substrate, and performing high-speed laser cladding on the substrate in a local inert gas protection atmosphere, zirconium carbide undergoes a phase change under the action of the high-energy laser beam to form an ultra-high temperature ceramic / refractory metal coating having both a ceramic phase and a metal phase; The process parameters of high-speed laser cladding were as follows: laser power was set to 2500 W, scanning rate was 80 mm / s, and overlap rate was 85%; S3. Ball milling to prepare powder for embedded siliconization process: S3-1, powder for embedded siliconization process, weigh 25% Si powder, 68% Al2O3 powder, 5% Y2O3 powder and 2% NaF powder according to the mass ratio; Si powder is used as silicon source, Al2O3 powder and Y2O3 powder are used as dispersants, and NaF powder is used as activator; Among them, the particle size of Si powder is 300 mesh, purity is 99.99%; the particle size of Al2O3 powder is 100 mesh, purity is 99.99%; the particle size of Y2O3 powder is 100 mesh, purity is 99.99%; the particle size of NaF powder is 100 mesh, purity is 99.99%; S3-2, placing the weighed powder raw material in a ball mill, using a planetary mill to grind the powder to fineness and mix it evenly, with a ball-to-material ratio of 2:1, a ball mill speed of 250r / min, and a ball milling time of 5h to obtain powder for embedded siliconization process; S4. Preparation of ultra-high temperature ceramic / refractory metal silicide composite coating by embedded siliconization process: S4-1: Cut the ultra-high temperature ceramic / refractory metal coating prepared in S2 into a 28mm×18mm×5mm rectangular block, and use sandpaper to remove the wire cutting marks on all surfaces of the sample except the surface where the coating is located, until the surface is flat, smooth and scratch-free; select a crucible with a capacity of 30ml, and in order to ensure a certain distance from the crucible mouth, the mixed infiltration dosage used for a single siliconization is 24g; S4-2: Take out the siliconized powder after ball milling in S3-2, weigh 12g and put it into the crucible for compaction, put the sample to be siliconized into the center area, and then weigh 10g of powder for embedding siliconization process to cover the sample and compact it, mix neutral alumina and silica sol in appropriate amounts to prepare a sealing slurry to seal the crucible cover and the crucible; put the sealed crucible on the corundum boat and push it to the center of the heating tube of the tubular furnace, so that the crucible is fixed in the highest temperature area during heating and insulation and is heated evenly; S4-3: Place the crucible on the corundum boat and place it in the center of the tube furnace. Evacuate the tube until the pressure inside the tube drops to 0.1MPa and continue to evacuate for 10 minutes, then turn off the mechanical pump; introduce argon until the pressure inside the tube rises to atmospheric pressure for 5 minutes, then start heating and continue ventilating; the argon flow rate is 100ml / min; set the heating and cooling programs of the tube furnace, the heating rate is 10℃ / min, the holding temperature is 1200℃, the holding time is 24h, the cooling rate is 10℃ / min, and it is cooled to room temperature to obtain a composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy; the obtained composite coating of ultra-high temperature ceramics and refractory metal silicides on the surface of a refractory alloy has a continuous multilayer structure, the top layer is (Zr, Ta)C-TaSi2, the transition layer is (Zr, Ta)C-Ta(W), and the coating has a metallurgical bonding interface with the substrate; the density is >98.5%, the thickness is ≥300μm, and the average hardness is >1568.34 Hv 0.5 , the highest hardness reaches 1673.67 Hv 0.5 , it can last for 300 seconds under plasma beam ablation conditions of 2000-2100℃ and completely protect the substrate from being damaged.
2. A composite coating of ultra-high temperature ceramic and refractory metal silicide on the surface of a refractory alloy, characterized in that: The method for preparing a composite coating of ultra-high temperature ceramics and refractory metal silicide on the surface of a refractory alloy as described in claim 1 is used to obtain the composite coating of ultra-high temperature ceramics and refractory metal silicide on the surface of a refractory alloy, wherein the composite coating has a continuous multilayer structure, the top layer is (Zr, Ta)C-TaSi2, the transition layer is (Zr, Ta)C-Ta(W), and the coating has a metallurgical bonding interface with the substrate; the density is >98.5%, the thickness is ≥300μm, and the average hardness is >1568.34 Hv 0.5 , the highest hardness reaches 1673.67 Hv 0.5 , it can last for 300 seconds under plasma beam ablation conditions of 2000-2100℃ and completely protect the substrate from being damaged.
Citation Information
Patent Citations
Strengthened and toughened ultrahigh-density ultrahigh-temperature ablation-resistant coating and preparation method thereof
CN111978088A
Ultrahigh-temperature anti-ablation layered composite coating on surface of refractory metal and preparation method of ultrahigh-temperature anti-ablation layered composite coating
CN118241182A
Method for customizing magnetic permeability of soft magnet and soft magnet obtained thereby
CN119013743A
Annular nuclear fuel rod
TW202326757A
AU2020100541A4